AB1244 Quality life in patients with rheumatic disease, non-rheumatic diseases and healthy population. (12th June 2018) - Cuervo, F.M.; ,; Santos, A.M.; Rueda, J.C.; Angarita, I.; Saldarriaga, E.L.; Giraldo, R.; Ballesteros, J.; Pelaez, I.; Forero, E.; Ramirez, J.; Toro, C.; et al.
Abstract : Background: Within public health strategies, the quality of life is a fundamental factor of intervention. The EQ-5D-3L is one of the most used instruments worldwide. Objectives: To describe the change in quality of life and functional limitation of patients with rheumatic diseases compared to a healthy population and patients with other systemic diseases. Methods: The EQ-5D-3L survey was used in 6693 people from 6 cities in Colombia. An analytical study was developed. Results: In general, the healthy population (n=1104) reported not to have problems according to the EQ-5D-3L (median: 98, 34). Of the non-rheumatic patients (n=642), 20% showed a moderate compromise because of pain and discomfort, as well as anxiety and depression. Twenty percent of patients with cardiovascular disease (n=53) reported moderate limitation for mobility. Patients with cardiovascular diseases reported moderate difficulties in carrying out daily activities. * The values of each of the dimensions of the instrument are expressed in% ** HBP: high blood pressure, CVD: cardiovascular disease, TB: tuberculosis *** Mental disorders: anxiety, nervousness or depression. Patients with rheumatic diseases (n=2274) manifested different degrees of limitation in mobility and daily activities. Patients with rheumatic diseases and comorbidities had greater compromise in quality of life predominately by pain and physical discomfort (more than 50% of the patients) figure 1. Conclusions: In comparison with general population, rheumatic patients had a lower quality of life, and it is even worse in patients with rheumatic diseases and comorbidities. Comprehensive care of rheumatic patients should include strategies to improve standards of quality of life such as mobility, to perform daily activities and management of problems such as pain and discomfort. There are specific factors of intervention to reduce long-term disability of patients with rheumatic diseases. Disclosure of Interest: None declared